Analysis of Added Value of Sagumi Products at the Sago Meambo Food Business Group (KU-SMF) - Vira Fahira; Bahari; Sitti Aida Adha Taridala (International Journal of Technology and Education Research, 2025)
This study aims to determine and analyze the Value Added generated by the sago meambo food business group in kendari city. This research was conducted in Purirano Village, Kendari District, Kendari City in April 2024. Types and sources of data using primary data and secondary data. Data collection techniques using interviews, observation and documentation techniques. The variables observed in this study are the production and marketing characteristics of KU-SMF. Including types of inputs (raw materials and other materials), input prices (raw material prices, equipment prices and packaging prices), output prices and output quantities (Krispy Sago Brownies, Benk-Benk, Moringa Leaf Sago Chips and Chocolate Sago Biscuits). The product with the highest added value is Chocolate Biscuits of Rp.173,834/kg, value-added ratio of 95%, and profit of Rp.165,834 /kg. The products produced are Moringa Leaf Sago Chips, Benk-Benk, Sago Chocolate Brownies and Chocolate Sago Biscuits